Analisis Efisiensi Hasil Pencacahan Terhadap Tipe Pencacah Dan Material Sampah - Adhe Anggry; Subkhan Subkhan (Manutech : Jurnal Teknologi Manufaktur, 2017)
Waste is one of the many social problems faced by the community. To solve the problem of waste required a technology to process waste itself. Several studies have been done, one of which is design and construction thrasher machine. There are several studies on the design and construction thrasher machine. However, the analysis was conducted on one type of thrasher machine with a particular waste material. This study aims to obtain the results of the efficiency analysis of the thrasher machine results on the type of thrasher machine and waste material. The method used is experimental method. The type of thrasher machine and waste material used as a free variable. The percentage of the chopping result is chosen as a variable depending on the speed of rotation and thrasher time as the companion variable. The results of this study based on the results of experiments, both qualitatively and quantitatively shows that plastic bottle trash has a suit with shear type, grass litter has a match with the type of swing and trash has a match with the type of crusher.